Insights into liquid phase sintering mechanism of high-alumina and low-silica hematite ores - Wanlong Fan; Zhiwei Peng; Tuo Pan; Huibo Liu; Shaochang Nie; Lin Xiong; Qiang Zhong; Mingjun Rao (Minerals Engineering, 2026)

A composite catalytic reforming electrode with perovskite catalyst and Ni foam for high efficient CH4-fueled solid oxide fuel cell - Wei Luo; Yong Yang; Qinzhong Chen; Mingjun Li; Peng Qiu; Manqing Yang; Kang Li; Yangbo Jia; Renhong Li; Tong Wei (Chemical Engineering Journal, 2026)

Decoupling of evapotranspiration from atmospheric demand: mechanistic insights into the local evaporation paradox in arid shrublands via physical and physiological resistance thresholds - Yuquan Qiang; Mingjun Zhang; Yu Zhang; Shengjie Wang; Xianying Xu; Jinchun Zhang; Guiquan Fu; Zhilan Wang; Meilin Sun; Peng Zhao; Shiquan Liu (Journal of Hydrology, 2026)

Activation of periodate driven by the synergistic interaction between inherent soil Fe and organic matter for adiazine degradation: Mechanisms, soil-type effects, and soil property changes - Yue Zhang; Caixia Yan; Yabing Chen; Yuyan Liu; Mingjun Ding; Peng Wang; Haofeng Liu; Minghua Nie (Journal of Hazardous Materials, 2026)

Cooling-regime regulation of rutile crystallization and enrichment in titanium-bearing electric arc furnace slag - Wanlong Fan; Zhiwei Peng; Fengming Yang; Huixian Bai; Jianzhi Zhang; Lingyun Yi; Mingjun Rao (Process Safety and Environmental Protection, 2026)

A fuel modification strategy for cleaner iron ore sintering: lime milk-derived calcium oxide coating of coke breeze for combustion regulation and multi-pollutant reduction - Wenzheng Jiang; Qiang Zhong; Fuliang Teng; Jie Liu; Zishuo Gao; Hongyun Yin; Liang Fan; Bin Xu; Mingjun Rao; Zhiwei Peng (Journal of Cleaner Production, 2026)

Mobile self-assembled membranes: A novel strategy for boosting light hydrocarbon separation efficiency - Yanan Jia; Zixuan Huang; Minglong Wang; Zhi Li; Hongyi Yu; Jun Xu; Bei Liu; Mingjun Deng; Jingming Li; Kun Li; Mingke Yang; Ruihang Zhang; et al. (Chemical Engineering Journal, 2026)

Physicochemical determinants of macrophyte selection by Pomacea canaliculata and the implications for lake restoration - Yinwei Gao; Jian Gao; Anni Dai; Junzhan Li; Yunfei Zhou; Jiahe Zhu; Kaida Peng; Yachan Ji; Heyun Wang; Mingjun Liao; Zhengwen Liu; Erik Jeppesen (Aquatic Sciences, 2026)

Enhanced selective leaching of Ni and Co via pre-oxidizing and high-pressure acid leaching of Ni-Co-Fe powder - Jing Chen; Yuqi Zhong; Jun Luo; Xin Zhang; Mingjun Rao; Zhiwei Peng; Guanghui Li; Tao Jiang (Hydrometallurgy, 2026)

Single adsorption and co-adsorption of aldehyde molecules over (111) surface of precious metal: A theoretical perspective evaluation - Zhengyun Zhang; Manmen Liu; Mingjun Peng; Kunhua Zhang; Xiaolong Zhou (Journal of Environmental Management, 2026)

PRSS23 functions downstream of ZEB1 to promote esophageal squamous cell carcinoma progression by driving M2 polarization of tumor associated macrophages - Wei Chen; Chanjuan Chen; Zhongyun Hu; Fanfan Li; Yao Peng; Mingjun Zhang (Molecular and Cellular Biochemistry, 2026)

Temperature-driven regime shifts in riverine bacterial communities: Machine learning identifies key thresholds and seasonal management implications - Ru Liu; Peng Wang; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang; Qinwei Chen; Wei Yang (Journal of Environmental Sciences, 2026)

Is expectation disconfirmation related to stakeholder satisfaction and willingness to engage in national parks? A case study of Shennongjia National Park in China - Yangyang Zhang; Zhen Fu; Yang Xiang; Chucai Peng; Mingjun Teng; Lixiong Zeng; Wanji Yang; Lei Pan; Pengcheng Wang (Forest Policy and Economics, 2026)

Identification and evaluation of odor emissions from a petrochemical production area in China - Yunxia Feng; Jinchan Peng; Yirong Guo; Qingrun Li; Anshan Xiao; Rui Dong; Dewu Ding; Mingjun Li (Atmospheric Pollution Research, 2026)

Low-temperature soda-ash roasting of ludwigite ore: Scale-up feasibility for magnetite and borax production - Jinxiang You; Xin Zhang; Mingjun Rao; Jun Luo; Zhiwei Peng; Guanghui Li (Journal of Environmental Chemical Engineering, 2025)

Study of 3D geological suitability evaluation via machine learning and gray correlation analysis - Xiaozheng Liu; Peng Zhang; Chang Xu; Dingfei Zhang; Zhaoxuan Dong; Mingjun Li (Earth Science Informatics, 2025)

Human traffic intensity alters the soil microbial community composition, diversity, and structure in subtropical urban green spaces - Abdul Baess Keyhani; Wei He; Mingjun Teng; Zhaogui Yan; Monira Fayaz; Zhaohui Peng; Yangyang Zhang; Safir Ahmad Tamim; Xiuyuan Wang; Zemin Han; Pengcheng Wang (Applied Soil Ecology, 2025)

Soil type-mediated root and leaf architectural modifications outweigh cadmium bioavailability in governing cadmium accumulation in rice - Gaoxiang HUANG; Jinbao ZHANG; Changfeng DING; Zhongyang XIONG; Jia LIU; Jingru HE; Haoyuan LÜ; Mingjun DING; Peng WANG; Yinghui JIANG; Lijun ZHOU; Zhenling LI (Pedosphere, 2025)

An equitable spatial strategy for urban green space based on reconciling growing and shrinking neighbourhoods at the parcel level - Cheng Sun; Xiaoqing Song; Jianquan Cheng; Mingjun Peng; Xiangmei Li (Land Use Policy, 2025)

Cross-altitude distribution patterns of bacterial communities in Chinese rivers: evidence from meta-analysis - Ru Liu; Peng Wang; Qinwei Chen; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang (Environmental Research, 2025)

“Peeling egg” strategies for regenerating spent graphite with tailored surface/sub-surface and removed impurities towards high capacity - Tianjing Wu; Chen Liu; Mingjun Jing; Wei Sun; Yue Yang; Honghui Hu; Peng Ge (Chemical Engineering Journal, 2025)

Rhizosphere microbiota modulate cadmium mobility dynamics and phytotoxicity in rice under differential Cd stress - Linxiu Cheng; Zhenling Li; Lijun Zhou; Jie Xie; Qiangqiang Zhou; Mingjun Ding; Peng Wang; Hua Zhang; Minghua Nie; Gaoxiang Huang (Plant and Soil, 2025)

Application of density functional theory methods for evaluating the adsorption capacity of carbonyl sulfide and sulfur dioxide on pristine and transition metal doped Ag(111) surfaces - Zhengyun Zhang; Manmen Liu; Mingjun Peng; Kunhua Zhang; Xiaolong Zhou (Journal of Environmental Chemical Engineering, 2025)

Double-confined FeCo nanoalloys as efficient and stable catalyst for selective hydrogenation of nitroarenes - Zhenyu Lei; Hao Sun; Lin Wu; Honglei Sun; Xiaomin Yang; Jingyao Liu; Peng Zhang; Mingjun Jia (Chemical Engineering Journal, 2025)

Thresholds for the relationships between soil trace elements and ecosystem multifunctionality in degraded alpine meadows - Yuping Wu; Mingjun Ding; Hua Zhang; Tiane Zou; Peng Huang; Huan Xu; Yueju Zhang; Huan Zeng; Jiaxin Xiong; Liyao Cheng; Linshan Liu; Yili Zhang (Agriculture, Ecosystems & Environment, 2025)

Mn-rich seedlings coupled with slow-release soil immobilization material effectively reduced cadmium accumulation in rice grain - Jinbao ZHANG; Zhongyang XIONG; Yurong WANG; Mingyue WU; Mingjun DING; Peng WANG; Zhenling LI; Gaoxiang HUANG (Pedosphere, 2025)

Selective enrichment of potential pathogens and antibiotic resistance genes derived from farmland residual microplastic films - Gaoxiang Huang; Hao Wang; Zhenling Li; Xiaokang He; Guangchun Shan; Peng Wang; Mingjun Ding; Chenghong Feng (Applied Soil Ecology, 2025)

Degradation mechanisms and restoration strategies of Haloxylon ammodendron Forests: Insights from water use and environmental stress - Yuquan Qiang; Mingjun Zhang; Yu Zhang; Xianying Xu; Jinchun Zhang; Guiquan Fu; Peng Zhao; Shengjie Wang (Agricultural and Forest Meteorology, 2025)

Effect of mineral fertilizer addition on Pinus massoniana Lamb leaf litter decomposition and on amino acid concentration in a subtropical forest - Abdul Baess Keyhani; Wei He; Mingjun Teng; Zhaogui Yan; Monira Fayaz; Peng Zhao Hui; Wang Xiuyuan; Zemin Han; Abebe Assefa Gobena; Ataeei Abdul Rasool; Pengcheng Wang (Plant and Soil, 2025)

Application of biomass energy in titanomagnetite reduction for Fe/Ti recycling: Overcoming the challenge of iron grain growth - Lingyun Yi; Xiaoshuai Shen; Yang Shu; Bing Deng; Qiang Zhong; Zhiwei Peng; Mingjun Rao; Guanghui Li; Tao Jiang (Fuel, 2025)

Global dry-wet patterns under various driving factors and their applications in projecting the future - Junjie Duan; Yu Li; Simin Peng; Yuxin Zhang; Zhansen Zhang; Mingjun Gao; Yaxin Xue; Hao Shang; Shiyu Liu (Quaternary International, 2025)

Facile and green synthesis of Ag/Cu bimetallic nanoparticles using waste banana peel extract for effective corrosion inhibition of mixed sulfate-reducing bacteria - Yuhua Su; Fuli Wu; Peng Xiao; Hang Zhang; Guanglei Lv; Mingjun Zhu; Qiyou Liu; Chaocheng Zhao (Journal of Environmental Management, 2025)

4-Nitrophenol at environmentally relevant concentrations mediates reproductive toxicity in Caenorhabditis elegans via metabolic disorders-induced estrogen signaling pathway - Jia Wang; Jiechen Yin; Danhong Peng; Xiaoqian Zhang; Zhouhong Shi; Weixi Li; Yingchi Shi; Mingjun Sun; Nan Jiang; Beijing Cheng; Xingchen Meng; Ran Liu (Journal of Environmental Sciences, 2025)

Analysis of the genetic basis of fiber-related traits and flowering time in upland cotton using machine learning - Weinan Li; Mingjun Zhang; Jingchao Fan; Zhaoen Yang; Jun Peng; Jianhua Zhang; Yubin Lan; Mao Chai (Theoretical and Applied Genetics, 2025)

Increasing human activity shifts the key spatial scale of landscape patterns on water quality from sub-basins to riparian zones - Jiawei Wen; Peng Wang; Yuanyang She; Mingjun Ding; Hua Zhang; Gaoxiang Huang; Minghua Nie (Science of The Total Environment, 2024)

Differential response of heavy metal accumulation in freshwater aquatic organisms to organic matter pathway (δ13C) and trophic level (δ15N) - Huan Zeng; Xiang Xu; Mingjun Ding; Hua Zhang; Yinghui Jiang; Peng Wang; Gaoxiang Huang (Environmental Pollution, 2024)

Boosting oxygen reduction reaction kinetics by Fe–V dual sites in ultrafine V-Fe3C nanoparticles for aluminum-air batteries - Shuya Zhang; Qiming Chen; Qianqiao Wang; Xinyu Luo; Mingjun Cen; Wenchao Peng; Yang Li; Qicheng Zhang; Xiaobin Fan (Chemical Engineering Journal, 2024)

Grifola frondosa polysaccharide's therapeutic potential in oxazolone-induced ulcerative colitis - Xiaoyi Liu; Mingjun Zhang; Shuai Chen; Huijuan Liu; Haoran Ma; Ting Hu; Peng Luo; Shaofeng Wei (Carbohydrate Polymers, 2024)

Spatial heterogeneity of soil moisture caused by drainage and its effects on cadmium variation in rice grain within individual fields - Gaoxiang Huang; Yu Wu; Linxiu Cheng; Dongmei Zhou; Xingxiang Wang; Mingjun Ding; Peng Wang; Yurong Wang (Science of The Total Environment, 2024)

Synergistic effects of mixed microorganisms on the corrosion of X65 carbon steel in actual reinjection water - Yuhua Su; Hang Zhang; Guanglei Lv; Fuli Wu; Peng Xiao; Mingjun Zhu; Chaocheng Zhao; Qiyou Liu (Journal of Environmental Chemical Engineering, 2024)

Dynamic patterns of particulate matter concentration and size distribution in urban street canyons: insights into diurnal and short-term seasonal variations - Xiaoshuang Wang; Xiaoping Chen; Zhixiang Zhou; Mingjun Teng; Yang Xiang; Chucai Peng; Chunbo Huang; Changhui Peng (Environmental Monitoring and Assessment, 2024)

Reduced internal stress of quasi-single crystalline Na4Fe3(PO4)2P2O7 electrode enhancing sodium-ion kinetics - Yukun Xi; Mingjun Wang; Guangjin Wang; Junqi Peng; Ningjing Hou; Zihao Yang; Xiaoxue Wang; Dongzhu Liu; Xiaohua Pu; Guiqiang Cao; Ruixian Duan; Qinting Jiang; et al. (Chemical Engineering Journal, 2024)

Tailoring tactics for preparation of superior thermal insulation materials from blast furnace ferronickel slag: Control of sintering temperature - Wanlong Fan; Zhiwei Peng; Tianle Yin; Chaojun Xiang; Huimin Tang; Lei Ye; Mingjun Rao (Process Safety and Environmental Protection, 2024)

Differential reduction behaviors of nickel and iron components in laterite ore under microwave irradiation - Huimin Tang; Zhiwei Peng; Tianle Yin; Lingyun Yi; Mingjun Rao (Journal of Environmental Chemical Engineering, 2024)

Particle sizes crucially affected the release of additives from tire wear particles during UV irradiation and mechanical abrasion - Taishuo Zhang; Mingjun Wang; Yingxuan Han; Jingxuan Liu; Zixuan Zhang; Mengjie Wang; Peng Liu; Shixiang Gao (Journal of Hazardous Materials, 2024)

Effects of particle size and AQDS on the flow of electron equivalents between magnetite and aqueous Fe2+ - Huan Peng; Zhenli Zhu; Carolyn I. Pearce; Anxu Sheng; Mingjun Nie; Alpha T. N'Diaye; Xin Zhang; Kevin M. Rosso; Juan Liu (Geochimica et Cosmochimica Acta, 2024)

Effect of pyrolysis temperature and molecular weight on characterization of biochar derived dissolved organic matter from invasive plant and binding behavior with the selected pharmaceuticals - Wangyu Wang; Minghua Nie; Caixia Yan; Yulong Yuan; Aoxue Xu; Mingjun Ding; Peng Wang; Min Ju (Environmental Pollution, 2024)

Co-utilization of electric arc furnace dust and copper slag for preparing zinc ferrite based on microwave roasting - Huimin Tang; Ran Tian; Zhiwei Peng; Zexi Gong; Tong Zhang; Guanwen Luo; Qiang Zhong; Mingjun Rao (Journal of Environmental Chemical Engineering, 2024)

Two-phase modelling of erosion and deposition process during overtopping failure of landslide dams using GPU-accelerated ED-SPH - Mingjun Zhou; Zhenming Shi; Chong Peng; Ming Peng; Kahlil Fredrick E. Cui; Bo Li; Limin Zhang; Gordon G.D. Zhou (Computers and Geotechnics, 2024)

Phase transformations and microstructure evolution of boron-containing iron concentrate during roasting under CO-CO2-N2 atmosphere: Synergistic effect of soda-ash and CO concentration - Jinxiang You; Meishi Hu; Mingjun Rao; Xin Zhang; Jun Luo; Zhiwei Peng; Guanghui Li (Minerals Engineering, 2024)

A novel WCO-MDI reactive rejuvenation method for aged SBS modified asphalt toward sustainable asphalt pavements - Yurou Zhang; Changjun Zhou; Ping Zou; Mingjun Hu; Peng Cao (Journal of Cleaner Production, 2024)

Visible light-mediated activation of periodate for bisphenol A degradation in the presence of Fe3+ and gallic acid at neutral pH - Yulong Yuan; Wangyu Wang; Minghua Nie; Caixia Yan; Peng Wang; Mingjun Ding (Chemical Engineering Journal, 2024)

Enhanced radiation heat transfer performance of Alumina-Spinel composite sphere with hollow structure for rapidly ultra-high temperature thermal storage/release process - Xin Zhou; Shenghao Liao; Seiji Yamashita; Mitsuhiro Kubota; Akihiro Takeuchi; Peng Gao; Mingjun Liu; Ruoxuan Li; Chaoyang Zhang; Hideki Kita (Chemical Engineering Journal, 2024)

Crocin alleviates neurotoxicity induced by bupivacaine in SH-SY5Y cells with inhibition of PI3K/AKT signaling - Lili Lin; Zhen Chen; Jun Li; Jianye Peng; Jian Wang; Mingjun Feng; Tiancheng Liu; Mengli Zhang; Xian Wu; Fen Ai; Caijie Shen (Genes & Genomics, 2024)

Recycling valuable metals from spent lithium-ion battery cathode materials based on microwave-assisted hydrogen reduction followed by grind-leaching and magnetic separation - Jinxiang You; Zhongxiao Qin; Gaohui Wang; Mingjun Rao; Jun Luo; Zhiwei Peng; Shang Zou; Guanghui Li (Journal of Cleaner Production, 2023)

Reduced soil multifunctionality and microbial network complexity in degraded and revegetated alpine meadows - Bobo Wu; Mingjun Ding; Hua Zhang; Adam Thomas Devlin; Peng Wang; Lu Chen; Yueju Zhang; Yang Xia; Jiawei Wen; Linshan Liu; Yili Zhang; Minhuang Wang (Journal of Environmental Management, 2023)

Platinum-group metals: Demand, supply, applications and their recycling from spent automotive catalysts - Huimin Tang; Zhiwei Peng; Ran Tian; Lei Ye; Jian Zhang; Mingjun Rao; Guanghui Li (Journal of Environmental Chemical Engineering, 2023)

SARS-COV-2 spike protein promotes RPE cell senescence via the ROS/P53/P21 pathway - Yuhang Zhang; Xuyan Peng; Mengjiao Xue; Jingjing Liu; Guohui Shang; Mingjun Jiang; Dandan Chen; Baixue Liu; Yuxuan Wang; Xiaolin Jia; Jianqing Xu; Fengyan Zhang; et al. (Biogerontology, 2023)
SARS-Cov-2 infection, which has caused the COVID-19 global pandemic, triggers cellular senescence. In this study, we investigate the role of the SARS-COV-2 spike protein (S-protein) in regulating the senescence of RPE cells. The results showed that administration or overexpression of S-protein in ARPE-19 decreased cell proliferation with cell cycle arrest at the G1 phase. S-protein increased SA-β-Gal positive ARPE-19 cells with high expression of P53 and P21, senescence-associated inflammatory factors (e.g., IL-1β, IL-6, IL-8, ICAM, and VEGF), and ROS. Elimination of ROS by N-acetyl cysteine (NAC) or knocking down p21 by siRNA diminished S-protein-induced ARPE cell senescence. Both administrated and overexpressed S-protein colocalize with the ER and upregulate ER-stress-associated BIP, CHOP, ATF3, and ATF6 expression. S-protein induced P65 protein nuclear translocation. Inhibition of NF-κB by bay-11-7082 reduced S-protein-mediated expression of senescence-associated factors. Moreover, the intravitreal injection of S-protein upregulates senescence-associated inflammatory factors in the zebrafish retina. In conclusions, the S-protein of SARS-Cov-2 induces cellular senescence of ARPE-19 cells in vitro and the expression of senescence-associated cytokines in zebrafish retina in vivo likely by activating ER stress, ROS, and NF-κb. These results may uncover a potential association between SARS-cov-2 infection and development of AMD.

Surface urban heat island mitigation network construction utilizing source-sink theory and local climate zones - Yang Xiang; Qingya Cen; Chucai Peng; Chunbo Huang; Changguang Wu; Mingjun Teng; Zhixiang Zhou (Building and Environment, 2023)

Time-scale effects in human-nature interactions, regionally and globally - Yu Li; Mingjun Gao; Zhansen Zhang; Yuxin Zhang; Simin Peng (Journal of Geographical Sciences, 2023)

A model based on immune-related lncRNA pairs and its potential prognostic value in immunotherapy for melanoma - Wenshuai Li; Yingxuan Zhan; Chong Peng; Zhan Wang; Tiantian Xu; Mingjun Liu (Functional & Integrative Genomics, 2023)

A meta-analysis reveals that geographical factors drive the bacterial community variation in Chinese lakes - Pengfei Gao; Peng Wang; Mingjun Ding; Hua Zhang; Gaoxiang Huang; Minghua Nie; Guangwei Wang (Environmental Research, 2023)

Degradation-driven bacterial homogenization closely associated with the loss of soil multifunctionality in alpine meadows - Yueju Zhang; Mingjun Ding; Hua Zhang; Nengyu Wang; Ziping Yu; Huan Xu; Peng Huang (Agriculture, Ecosystems & Environment, 2023)

Introduction of the FecG mutation in GDF9 gene via CRISPR/Cas9 system with single-stranded oligodeoxynucleotide - Xin Xu; Xuemei Zhang; Xinrong Peng; Chunjie Liu; Wenrong Li; Mingjun Liu (Theriogenology, 2023)

Release of millions of micro(nano)plastic fragments from photooxidation of disposable plastic boxes - Fugeng Zha; Jiamin Dai; Yinxuan Han; Peng Liu; Mingjun Wang; Haiyong Liu; Xuetao Guo (Science of The Total Environment, 2023)

Characterization of copper binding to biochar-derived dissolved organic matter: Effects of pyrolysis temperature and natural wetland plants - Caixia Yan; Wangyu Wang; Minghua Nie; Mingjun Ding; Peng Wang; Hua Zhang; Gaoxiang Huang (Journal of Hazardous Materials, 2023)

Energy-saving production of high value-added foamed glass ceramic from blast furnace slag and hazardous wastes containing heavy metal ions - Mingjun Li; Feng Zheng; Jiao Wang; Donghua Jia; Xiaodong Mao; Peng Li; Qiang Yuan; Qiang Zhen; Yi Yu (Journal of Cleaner Production, 2023)

Comprehensive proteomic and phosphoproteomic reveal that Microcystin-LR contributed to the malignant progression of gastric cancer by estrogenic potency - Peiyan Yang; Peng Zhang; Yali Deng; Yinghao Liao; Xinxin Guo; Mingjun Sun; Lihong Yin; Ran Liu (Environmental Pollution, 2023)

Potential of granular complexes of lime and montmorillonite for stabilizing soil cadmium and the underlying mechanisms - Gaoxiang Huang; Keyi Huang; Xingxiang Wang; Wuxing Shu; Wenjing Ren; Peng Wang; Hua Zhang; Minghua Nie; Mingjun Ding (Environmental Pollution, 2023)

Solar light promoted degradation of bisphenol s in carbonate/peroxymonosulfate system through accelerating singlet oxygen generation - Yulong Yuan; Minghua Nie; Caixia Yan; Leliang Wu; Wenbo Dong; Mingjun Ding; Peng Wang (Chemical Engineering Journal, 2023)

Hydrogen sulfite promoted the activation of persulfate by μM Fe2+ for bisphenol A degradation - Shiyao Chen; Caixia Yan; Minghua Nie; Leliang Wu; Mingjun Ding; Peng Wang (Environmental Science and Pollution Research, 2022)

The Mitochondrial-Derived Peptide MOTS-c Attenuates Oxidative Stress Injury and the Inflammatory Response of H9c2 Cells Through the Nrf2/ARE and NF-κB Pathways - Caijie Shen; Jian Wang; Mingjun Feng; Jianye Peng; Xiangfeng Du; Huimin Chu; Xiaomin Chen (Cardiovascular Engineering and Technology, 2022)

Spectral characteristic of the waters with different sizes of particles: impact of water quality and land-use type - Zelan Lv; Peng Wang; Caixia Yan; Minghua Nie; Xiaoying Xiong; Mingjun Ding (Environmental Science and Pollution Research, 2022)

The Antioxidant Role of Selenium via GPx1 and GPx4 in LPS-Induced Oxidative Stress in Bovine Endometrial Cells - Samson O. Adeniran; Peng Zheng; Rui Feng; Elikanah O. Adegoke; Fushuo Huang; Mingjun Ma; Ziming Wang; Olamigoke O. Ifarajimi; Xiaoyu Li; Guixue Zhang (Biological Trace Element Research, 2022)

Genetic variation and differentiation of Quercus variabilis populations at phosphate and non-phosphate rock sites in southwestern China - Huawei Ji; Baoming Du; Hongmei Du; Ningxiao Sun; Xu Yang; Mingjun Peng; Hongzhang Kang; Shan Yin; Chunjiang Liu (Plant Systematics and Evolution, 2021)

A Hu sheep genome with the first ovine Y chromosome reveal introgression history after sheep domestication - Ran Li; Peng Yang; Ming Li; Wenwen Fang; Xiangpeng Yue; Hojjat Asadollahpour Nanaei; Shangquan Gan; Duo Du; Yudong Cai; Xuelei Dai; Qimeng Yang; Chunna Cao; et al. (Science China Life Sciences, 2021)

Stability analysis of the Xinlu Village landslide (Chongqing, China) and the influence of rainfall - Luqi Wang; Yueping Yin; Zhihua Zhang; Bolin Huang; Yunjie Wei; Peng Zhao; Mingjun Hu (Landslides, 2019)

Spatial characterization, risk assessment, and statistical source identification of the dissolved trace elements in the Ganjiang River—feeding tributary of the Poyang Lake, China - Hua Zhang; Yinghui Jiang; Min Wang; Peng Wang; Guangxun Shi; Mingjun Ding (Environmental Science and Pollution Research, 2017)